2007
DOI: 10.1063/1.2717585
|View full text |Cite
|
Sign up to set email alerts
|

Coupling interaction in 1-3-type multiferroic composite thin films

Abstract: Using the time-dependent Ginzburg-Landau equation, the coupling interaction of the ferroelectric (FE) and ferromagnetic (FM) phases in epitaxial 1-3-type multiferroic thin films was investigated considering the effect of elastic stress arising from the FE/FM and film/substrate interfaces. The result of the authors shows that the maximum polarization and magnetization appear with the FM fractions of 70% and 30%, respectively. The significant changes of the FE and FM properties are caused by the special structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…[ 96 ] The calculations revealed that the 1-3 type vertical heterostructures could exhibit large ME response which is even larger than that in their bulk counterparts if there is no leakage problem, while the 2-2 type layered heterostructures show much weaker ME coupling if assuming complete inplane constraint effect. Later on, similar theoretical results were also obtained by Landau-Ginsburg-Devonshire phenomenological thermodynamic theory [97][98][99][100][101] and phase-fi eld model. [106][107][108] The phase-fi eld simulation illustrates that the magnetic-fi eldinduced electric polarization is highly dependent on the fi lm thickness, morphology of the composite fi lms, and substrate constraint, which provides a number of degrees of freedom in controlling coupling in nanocomposite fi lms.…”
Section: Growth Of Me Composite Thin Filmssupporting
confidence: 53%
See 1 more Smart Citation
“…[ 96 ] The calculations revealed that the 1-3 type vertical heterostructures could exhibit large ME response which is even larger than that in their bulk counterparts if there is no leakage problem, while the 2-2 type layered heterostructures show much weaker ME coupling if assuming complete inplane constraint effect. Later on, similar theoretical results were also obtained by Landau-Ginsburg-Devonshire phenomenological thermodynamic theory [97][98][99][100][101] and phase-fi eld model. [106][107][108] The phase-fi eld simulation illustrates that the magnetic-fi eldinduced electric polarization is highly dependent on the fi lm thickness, morphology of the composite fi lms, and substrate constraint, which provides a number of degrees of freedom in controlling coupling in nanocomposite fi lms.…”
Section: Growth Of Me Composite Thin Filmssupporting
confidence: 53%
“…[96][97][98][99][100][101][102][103][104][105][106][107][108][109] The former has provided routes for novel structures and phases, and have the properties of traditional functional materials modifi ed by strain engineering. The latter has aided in the design of new multiferroics, and helped understanding of the coupling between magnetic and ferroelectric orders.…”
Section: Growth Of Me Composite Thin Filmsmentioning
confidence: 99%
“…Th e renaissance of multiferroic ME fi lms has recently been accelerated by advances in thin-fi lm growth techniques, such as the pioneering work of Zheng et al [7], supported by improved theoretical calculations [8][9][10][11][12]. Th e new growth techniques have provided routes to novel structures and phases, and allow the properties of traditional functional materials to be modifi ed by strain engineering.…”
mentioning
confidence: 99%
“…The ferroelectric thin films can be applied in MEMS, sensors and actuators, and so on [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It is well known that the interface coupling and the interactions among the layers in the multilayer structures can strongly affect the films' electrical properties, and an appropriate combination of the layers with different compositions can improve or create functional properties [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%